(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Prior to 1970s before the UN Conference on Human Environment, environment did not find much mention in the legal regime of any country, let alone the environmental courts. The concept of “environmental courts” emerged, firstly in Europe. The reason behind the increasing numbers of ECTs are multifarious, like the new international developments taking place in the world which are highlighting the grave concerns related to the environment, the increasing interaction and inter-dependence of environmental rights and human rights, the emerging novel threats to the environment in the form of climate change and others. ECTs deal only with the environmental cases and it uses the otherwise less-used techniques of alternative dispute resolution which are often cheaper and less time-consuming. These can be courts (judicial approach) or tribunals (executive or administrative approach), depending upon the societal, economic, political and environmental factors existing in a particular country. India saw the birth of NGT after a lot of deliberations within the legislative and judicial spheres. It was the result of the ratification of the path breaking Stockholm Conference, 1972 by India. The NGT through the balanced-approach towards the environment and economy, in plethora of cases, has won accolades from the civil society as well as from the centre, which is very much evident from the recent verdict and proceedings of the tribunal. But, setting up of an ECT is not the end of the road, but it’s an initial step in the direction of environmental justice which alone cannot guarantee the same but needs to be supplemented through various other means.